Joint Attention, Social-Cognition, and Recognition Memory in Adults - Kim, Kwanguk; Mundy, Peter (Frontiers in Human Neuroscience, 2012)
The early emerging capacity for Joint Attention (JA), or socially coordinated visual attention, is thought to be integral to the development of social-cognition in childhood. Recent studies have also begun to suggest that JA affects adult cognition as well, but methodological limitations hamper research on this topic. To address this issue we developed a novel virtual reality paradigm that integrates eye-tracking and virtual avatar technology to measure two types of JA in adults, Initiating Joint Attention (IJA) and Responding to Joint Attention (RJA). Distinguishing these types of JA in research is important because they are thought to reflect unique, as well as common constellations of processes involved in human social-cognition and social learning. We tested the validity of the differentiation of IJA and RJA in our paradigm in two studies of picture recognition memory in undergraduate students. Study 1 indicated that young adults correctly identified more pictures they had previously viewed in an IJA condition (67%) than in a RJA (58%) condition, η2 = 0.57. Study 2 controlled for IJA and RJA stimulus viewing time differences, and replicated the findings of Study 1. The implications of these results for the validity of the paradigm and research on the affects of JA on adult social-cognition are discussed.